REPRESENTASI NILAI SOSIAL DALAM CERPEN “ORANG-ORANG ANEH DARI SELATAN” KARYA NI KOMANG ARIANI : Kajian Sosiologi Sastra terhadap Nilai-Nilai Sosial dalam Karya Sastra Kontemporer - Marlina Marlina; Suhartini Khalik; M. Nurzin R. Kasau (JURNAL SKRIPTA, 2026)
Literary works are a form of creative expression of authors that contain various life values, such as religious, social, cultural, and moral values, which contribute to character formation and can be used as a learning tool. Literature has a close relationship with people's lives because it is able to reflect social reality and life dynamics through the experiences of characters and the conflicts presented. This study aims to reveal the representation of social values ​​in the short story "Orang-Orang Aneh dari Selatan" by Ni Komang Ariani using a sociological literary approach. This study focuses on five main aspects, namely socio-religious, educational, economic, political, and the function of social values ​​in people's lives. The method used is a qualitative approach with a descriptive research type. The main data were obtained from the short story text, while supporting data came from literary theory books, scientific articles, journals, and relevant previous research. Data collection techniques were carried out through in-depth reading, recording, and documentation. Data analysis was carried out through the stages of reduction, presentation, drawing conclusions and verification. The results of the study indicate the existence of five categories of social values, including socio-religious aspects (three data), education (five data), economic (six data), political (two data), and the function of social values ​​in society (eleven data). Thus, this short story represents various social values ​​that reflect the reality of life and has the potential to be a medium for character and social learning..